Physical Complaints of Pain and Heartburn as Part of The Symptoms of Somatization - Era Catur Prasetya; Intan Afifah; Muhammad Hanun Mahyuddin; Ulaa Haniifah; Khadijah Hasanah Abang Abdullah (Department of Psychiatry, Faculty of Medicine Universitas Airlangga, 2024)
Jurnal Psikiatri Surabaya, Volume 12 Issue 2 Page (186–193)